Demography, trade and state power: a tripartite model of medieval farming/language dispersals in the Ryukyu Islands - Jarosz, Aleksandra; Robbeets, Martine; Fernandes, Ricardo; Takamiya, Hiroto; Shinzato, Akito; Nakamura, Naoko; Shinoto, Maria; Hudson, Mark (Evolutionary human sciences, 2022)
Hunter-gatherer occupations of small islands are rare in world prehistory and it is widely accepted that island settlement is facilitated by agriculture. The Ryukyu Islands contradict that understanding on two counts: not only did they have a long history of hunter-gatherer settlement, but they also have a very late date for the onset of agriculture, which only reached the archipelago between the eighth and thirteenth centuries AD. Here, we combine archaeology and linguistics to propose a tripartite model for the spread of agriculture and Ryukyuan languages to the Ryukyu Islands. Employing demographic growth, trade/piracy and the political influence of neighbouring states, this model provides a synthetic yet flexible understanding of farming/language dispersals in the Ryukyus within the complex historical background of medieval East Asia.